Influence of anthropometric, ball impact and landing location parameters on serve velocity in elite tennis competition - Baiget, Ernest; Corbi, Francisco; López, José (Biology of Sport, 2023)
This study aimed (i) to analyse the associations between serve velocity (SV) and anthropometric, ball impact and landing location parameters in total serves (TS) and fastest serves (FS) performed during an ATP Tour event; (ii) to observe differences between first (S1) and second (S2) serves, and (iii) to determine a SV prediction model based on the relationship between the observed variables. Using Foxtenn technology, 30 S1 and 15 S2 were registered in 14 matches in twenty-one male professional tennis players. Ball impact (impact height [IH], impact projection angle [IPA] and relative impact height [RIH]), bounce landing (width and depth) location parameters, S1 and S2 SV in TS (TSV1 and TSV2) and FS (FSV1 and FSV2) alongside anthropometric characteristics of tennis players (body height [BH], body mass [BM] and body mass index [BMI]) were analysed. Significant moderate to large associations were found between BH and BM and TSV1, FSV1 and FSV2 (r = 0.315 to 0.593; p < 0.001), and between IH and IPA and TSV1 and TSV2 (r = 0.294 to -0.409; p < 0.001). BH and BM were the unique significant contributors of FS explaining 22 to 35% of FSV1 and FSV2. Only BM appears in the model to predict FSV1 and FSV2 (r2 = 0.48 and 0.21). We concluded that all three anthropometric, ball impact and bounce landing location parameters small to moderately influence TSV. Anthropometric parameters show an impact on SV when tennis players serve at or near maximal speed, highlighting the influence of BM above BH.